RELIABLE SPECTROSCOPIC ANALYTICAL PROCEDURE FOR QUANTITATIVE ESTIMATION OF OSIMERTINIB MESYLATE IN LIPOSOMAL DRY POWDER INHALER FORMULATION - PATIL, MANSING; PATEL, PINKAL (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of the present study was to develop an economical UV spectrophotometric method with a simple, rapid, accurate, precise, sensitive, and reproducible for the quantitative estimation of Osimertinib Mesylate (OM) in bulk and newly prepared Liposomal Dry Powder Inhaler (LDPI) formulation which has not been reported earlier. Methods: Different dilutions were prepared in methanol in the range of 4-16 µg/ml, scanned between 400-200 nm, and determined the maximum absorbance was to confirm the drug’s λmax. Linearity, accuracy, precision, the limit of detection (LOD), and the limit of quantitation (LOQ) were used as parameters to validate the method. The concentration of the OM was calculated based on a linear regression equation of the calibration curve. Results: The UV spectrum of OM showed λmax at 267 nm and a linear calibration curve with a regression coefficient (R2) of more than 0.997. The RSD for recovery studies was found ˂ 2 % and confirmed the accuracy of the proposed method. The LOD and LOQ were observed at 0.021 µg/ml and 0.063 µg/ml, respectively for bulk and 0.056 µg/ml and 0.170 µg/ml for OM LDPI formulation. The method was found to be precise with an RSD ˂ 2 %. Conclusion: The present UV spectrophotometric method can be used to successfully estimate OM in LDPI, and there is no interference of excipients during the study. The method is validated in compliance with International Conference on Harmonization (ICH) guidelines and it should be used as a routine quality control analysis i.e., assay for such dosage forms.